SVETO I PROFANO U MARINKOVIĆEVOJ „GLORIJI” (Philological Studies, 2019)
In this paper, The Sacred and the Profane in Marinković’s „Gloria”, the interpreted tragic rhythm of action is based on the geometry of motives composed of contrasted sacred and profane semantic elements. They are contextualized in two opposing semantic realistic / dramatic spaces - the cathedral and the circus. I interpret the ratio of the sacred and the profane in a broader context that applies not only to the dramaturgic function as it points to philosophy, particularly the philosophy of religion, but also anthropology and symbology. The relationship in this drama is much more complicated if viewed from a specific point of view (for example those offered by Mircea Eliade and Nikos Čausidis) that deepen the central problem of interest to some findings that were not previously present in the interpretation of this drama by Ranko Marnković. Especially the questioning of the circus and circus acts could lead us to a discussion about the "archetypal visual and mythical-symbolic premodels" and a different relation compared to what is routinely considered different in the interpretation of the sacred and the profane in this drama.
Keywords: croatian drama, theatre, Ranko Marinković, sacred, profane, religion